Acute effect of resistance exercises performed at diferente intensities on the hemodynamics of normotensive men - Saldanha, Mauricio Assis (2016)
The aim of this study was to investigate the acute effect of resistance exercise performed at different intensities on the hemodynamics of normotensive men. The study included 10 normotensive and recreationally-trained men (25.40 ± 6.90 years) performed the following three experimental protocols in a randomized order: a) 60% of 8RM; b) 80% of 8RM; c) 100% of 8RM. All protocols performed six exercises (Leg Press, Vertical Bench Press, Leg Flexion, Close-Grip Seated Row, Leg Extension and Shoulder Press) with three sets of eight repetitions for each exercise. Systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR) and double product (DP) were measured at rest, at the end of exercise and during the 60-minute post-exercise. The findings showed that there was a significant reduction in the faster SBP with a longer duration (p< 0.0001) for the 100% of 8RM intensity, but without significant decreases in DBP for all intensities (p> 0.05). There were significantly higher elevations in HR and DP for 100% of 8RM at all times s (p<0.0001). We conclude that high intensities (100% of 8RM) promote post-exercise hypotension with faster responses and greater duration and increase HR and DP in normotensive men.